2019
DOI: 10.1016/j.dld.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Deep remission on magnetic resonance imaging impacts outcomes of perianal fistulizing Crohn’s disease

Abstract: Background:The long-term management of perianal Crohn's disease for patients on anti-TNF-α therapy remains challenging. Aim: To evaluate the long-term course and complications of patients with perianal fistulas treated with anti-TNF-α based on their clinical remission and healing on MRI. Methods: Patients were evaluated clinically and by MRI. Deep remission was defined as clinical remission associated with the absence of contrast enhancement and T2 hyperintensity on MRI. Flare-free survival, surgery and hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…One additional patient achieved this endpoint at week 60, resulting in a total of 4 out of 20 (20%) patients with a fibrotic complex. This is an important finding, because deep remission on MRI is associated with a low chance of recurrence of perianal disease 26 . This long‐term effect helps justify the duration and the cost of the treatment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One additional patient achieved this endpoint at week 60, resulting in a total of 4 out of 20 (20%) patients with a fibrotic complex. This is an important finding, because deep remission on MRI is associated with a low chance of recurrence of perianal disease 26 . This long‐term effect helps justify the duration and the cost of the treatment.…”
Section: Discussionmentioning
confidence: 89%
“…This is an important finding, because deep remission on MRI is associated with a low chance of recurrence of perianal disease. 26 This long‐term effect helps justify the duration and the cost of the treatment. Furthermore, a completely fibrotic fistula complex is a relatively rare outcome of treatment, especially for medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed a predominantly, but not completely, fibrotic tract in another 30% of patients. Chambaz et al [19] found that deep remission (clinical remission and absence of enhancement on MRI) is associated with higher flare-free survival, but the value of a predominantly, but not completely, fibrotic tract on MRI is unknown. Only one retrospective study reports this feature after anti-TNF treatment, with predominant fibrosis being seen in only 3 out of 30 patients within 18 months [20].…”
Section: Discussionmentioning
confidence: 99%
“… 15–18 Generally, a completely fibrotic tract is considered as radiological healing. 15 , 17 Although it has been shown that a completely fibrotic tract is associated with a longer flare-fee period, 17 one can speculate that a largely but not completely fibrotic tract at imaging may be the representation of a possibly irreversible process of fibrosis development. Therefore, a largely fibrotic tract may have a similar predictive value for future long-term closure comparable to that of completely fibrotic tracks.…”
Section: Introductionmentioning
confidence: 99%